Epstein-Barr virus infection and expression of B-cell oncogenic markers in HIV-related diffuse large B-cell lymphoma - Chao, Chun (2012)
BACKGROUND: Epstein-Barr virus (EBV)-mediated lymphomagenesis in the setting of HIV infection has been widely accepted. However, little is known about how EBV impacts prognosis. We investigated the hypothesis that EBV infection is associated with expression of specific B-cell oncogenic markers in HIV-related diffuse large B-cell lymphoma (DLBCL), and examined the prognostic utility of detecting EBV infection. STUDY DESIGN: HIV-related DLBCL cases diagnosed between 1996–2007 within Kaiser Permanente California were identified. Immunohistochemistry staining was used to analyze the expression of selected markers that are cell cycle regulators, B-cell activators, and anti-apoptotic proteins among others. EBV infection was determined by in situ hybridization of EBV RNA. Correlations between EBV and marker expression were examined using Spearman’s correlation coefficient. The prognostic utility of EBV status was examined in multivariable Cox model adjusting for international prognostic index (IPI). Receiver-operating characteristics (ROC) analysis was used to evaluate improvement in model discrimination. RESULTS: Seventy HIV-related DLBCL cases were included (31% EBV+). EBV+ tumor was associated with increased expression of BLIMP1 and CD30, and reduced expression of BCL6 and LMO2. EBV+ tumor was independently associated with elevated 2-year overall mortality [hazard ratio=3.3 (95% CI: 1.6–6.6)]. Area under the ROC curve demonstrated improved model discrimination when incorporating tumor EBV status with IPI in the prediction model [0.65 vs. 0.74 (IPI only)]. CONCLUSION: Our results suggest that EBV infection was associated with expression of several tumor markers that are involved in the NF-κB pathway, and that detecting tumor EBV status may have prognostic utility in HIV-related DLBCL.